Transformational Leadership and the Strengthening of Positive School Culture Based on Minangkabau Local Values - Defril Syafrin; Nurhizrah Gistituati; Rusdinal Rusdinal; Nellitawati Nellitawati (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study examines how the integration of principals’ transformational leadership with Minangkabau cultural values serves as a constructive strategy for strengthening a positive school culture. The study addresses a gap in the literature, as research on transformational leadership has largely adopted a general perspective and has rarely explored its integration with local cultural values, despite the strong influence of Minangkabau traditions on leadership practices, social behavior, and character development in West Sumatra. A qualitative case study approach was employed. Data were collected through classroom and school observations, in-depth interviews with 12 participants, including the principal, teachers, and students, as well as document analysis. The findings reveal that transformational leadership is reflected in the development of a shared vision, inspirational communication, moral role modeling, and participatory decision-making. Core Minangkabau values, including bajanjang naiak, batanggo turun, duduak marundak, tagak maimpok, and the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah, are meaningfully embedded in leadership practices and character education. In addition, the Local Content Program on Minangkabau Culture functions as a strategic medium for transmitting cultural values, ethical principles, and student character. The integration of transformational leadership and local wisdom fosters a collaborative school culture, strengthens discipline through moral awareness, and promotes respectful, culturally grounded student character. The novelty of this study lies in proposing a culturally grounded model of transformational leadership based on Minangkabau values, offering a contextual framework for cultivating positive school culture and informing educational leadership policies in culturally diverse settings.